A Systematic Review and Meta-analysis of the Impact of Local Therapies on Local Event Suppression in Metastatic Hormone-sensitive Prostate Cancer - Tsuboi, Ichiro; Matsukawa, Akihiro; Kardoust Parizi, Mehdi; Klemm, Jakob; Mancon, Stefano; Chiujdea, Sever; Fazekas, Tamás; Miszczyk, Marcin; Laukhtina, Ekaterina; Kawada, Tatsushi; Katayama, Satoshi; Iwata, Takehiro; et al. (European urology oncology, 2024)
CONTEXT: It remains unclear to what extent the therapy of the primary local tumor, such as radical prostatectomy (RP) and radiation therapy (RT), improves overall survival in patients with low-volume metastatic hormone-sensitive prostate cancer (mHSPC). However, data suggest a benefit of these therapies in preventing local events secondary to local tumor progression. OBJECTIVE: To evaluate the efficacy of adding local therapy (RP or RT) to systemic therapies, including androgen deprivation therapy, docetaxel, and/or androgen receptor axis-targeted agents, in preventing local events in mHSPC patients compared with systemic therapy alone (ie, without RT of the prostate or RP). EVIDENCE ACQUISITION: Three databases and meeting abstracts were queried in November 2023 for studies analyzing mHSPC patients treated with local therapy. The primary outcome of interest was the prevention of overall local events (urinary tract infection, urinary tract obstruction, and gross hematuria) due to local disease progression. Subgroup analyses were conducted to assess the differential outcomes according to the type of local therapy (RP or RT). EVIDENCE SYNTHESIS: Overall, six studies, comprising two randomized controlled trials, were included for a systematic review and meta-analysis. The overall incidence of local events was significantly lower in the local treatment plus systemic therapy group than in the systemic therapy only groups (relative risk [RR]: 0.50, 95% confidence interval [CI]: 0.28-0.88, p = 0.016). RP significantly reduced the incidence of overall local events (RR: 0.24, 95% CI: 0.11-0.52) and that of local events requiring surgical intervention (RR: 0.08, 95% CI: 0.03-0.25). Although there was no statistically significant difference between the RT plus systemic therapy and systemic therapy only groups in terms of overall local events, the incidence of local events requiring surgical intervention was significantly lower in the RT plus systemic therapy group (RR: 0.70, 95% CI: 0.49-0.99); local events requiring surgical intervention of the upper urinary tract was significantly lower in local treatment groups (RR: 0.60, 95% CI: 0.37-0.98, p = 0.04). However, a subgroup analysis revealed that neither RP nor RT significantly impacted the prevention of local events requiring surgical intervention of the upper urinary tract. CONCLUSIONS: In some patients with mHSPC, RP or RT of primary tumor seems to reduce the incidence of local progression and events requiring surgical intervention. Identifying which patients are most likely to benefit from local therapy, and at what time point (eg, after response of metastases), will be necessary to set up a study assessing the risk, benefits, and alternatives to therapy of the primary tumor in the mHSPC setting. PATIENT SUMMARY: Our study suggests that local therapy of the prostate, such as radical prostatectomy or radiotherapy, in patients with metastatic hormone-sensitive prostate cancer can prevent local events, such as urinary obstruction and gross hematuria.
Keywords: Prostatic Neoplasms; prostatektomie; metastázy nádorů; lidé; antagonisté androgenů; mužské pohlaví; Neoplasm Metastasis; Male; kombinovaná terapie; Combined Modality Therapy; nádory prostaty; Androgen Antagonists; Prostatectomy; Humans